2006
DOI: 10.1542/peds.2005-2085
|View full text |Cite
|
Sign up to set email alerts
|

One Dose of Varicella Vaccine Does Not Prevent School Outbreaks: Is it Time for a Second Dose?

Abstract: Although disease was mostly mild, the outbreak lasted for approximately 2 months, suggesting that varicella in vaccinated persons was contagious and that 99% varicella vaccination coverage was not sufficient to prevent the outbreak. This investigation highlights several challenges related to the prevention and control of varicella outbreaks with the 1-dose varicella vaccination program and the need for further prevention of varicella through improved vaccine-induced immunity with a routine 2-dose vaccination p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
109
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 21 publications
5
109
1
3
Order By: Relevance
“…This study confirms that children vaccinated with a single-dose of varicella vaccine may both contract and transmit varicella, and high singledose varicella vaccination coverage may not provide sufficiently high population immunity to prevent outbreaks [10][11][12][13]. This study also demonstrates, as have others, that single-dose varicella vaccination is highly effective in preventing cases and mitigating the severity of breakthrough cases that occurs [9].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study confirms that children vaccinated with a single-dose of varicella vaccine may both contract and transmit varicella, and high singledose varicella vaccination coverage may not provide sufficiently high population immunity to prevent outbreaks [10][11][12][13]. This study also demonstrates, as have others, that single-dose varicella vaccination is highly effective in preventing cases and mitigating the severity of breakthrough cases that occurs [9].…”
Section: Discussionsupporting
confidence: 75%
“…During the single-dose varicella vaccination era in the United States, attack rates in school settings with high and low varicella vaccination coverage differed dramatically, from 9% to 15% in schools with coverage levels higher than 95% to 55% in a school with vaccination coverage of just 45% [6,[11][12][13][14]. In China, comparisons of areas with high varicella vaccination coverage to those with low coverage or no varicella vaccination also clearly demonstrate the impact of varicella vaccination on reducing attack rates during outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a mathematical model published in 1994 suggested that partial varicella vaccine coverage of the population had the potential to increase the incidence of varicella among adolescents and adults, even if it resulted in a decrease in the incidence of varicella in children. 6 Varivax [8][9][10] leading to a recommendation for a second dose of the vaccine at 4 to 6 years of age by the ACIP in 2006. 11 Recent studies have revealed that varicella incidence has declined further since implementation of the second dose 12,13 and effectiveness of the 2-dose series has been estimated to be as high as 98%, 14 confirming findings from clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…3,[12][13][14] Although this decreased the morbidity and mortality due to varicella, outbreaks were frequently reported among the vaccinated population. [15][16][17] The controversial causes of breakthrough infections were the age at vaccination, vaccine type, primary vaccine failure (not mounting protective immunity), or secondary vaccine failure (waning of protective immunity). 17,18 In response to breakthrough infections, a necessity to administer a second dose of the vaccine has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In response to breakthrough infections, a necessity to administer a second dose of the vaccine has emerged. 16,19,20 Watson reported that a second dose would provide higher antibody levels. 21 The Advisory Committee on Immunization Practices had recommended a second dose of varicella vaccine at 4-6 y of age (first dose at 12-15 months and second at 4-6 years) in the United States in 2006, 22 and the German Standing Committee on Vaccination had recommended a second dose varicella vaccine at 15-23 months of age (first dose at 11-14 months and second at 15-23 months, with a minimum 4-week interval) in Germany, in 2009.…”
Section: Discussionmentioning
confidence: 99%